Place des sports outdoor dans le développement touristique de la région Nord-Pas-de-Calais - Christian Dorvillé; Malek Bouhaouala (Territoire en Mouvement)
The area Nord-Pas-de-Calais within the framework of its economic reconversion emphasizes its asset of the tourist development. An exploratory study, starting from directing semi talks, aims at knowing if sporting tourism mainly based on the sporting ludo practices outdoor is part of the major concerns of the operators of regional tourism. The analysis of contents shows that sporting dimension does not seem yet a significant factor in the tourist attractivity of a territory : entertaining potential under estimated, lack of dialogue between the public and deprived actors (associative and commercial), little structured external communication, etc. In reference to the 2004 regional elections and the new law of decentralization we are not able to signal new change of the tourism development situation.